Strengthening Reflective Thinking Ability of Junior High School Students Using Weblog Media - Rahmadianti, Putri; Suryawati, Evi; Natalina. L, Mariani; Feniwati, Feniwati (Bioedukasi: Jurnal Pendidikan Biologi, 2021)
This research aims to develop weblog media about environmental contamination material to determine the reflective thinking skills of junior high school students. The development of a weblog as a learning medium used the ADDIE model. In this research up to the development phase. The weblog design has gone through the validation phase. The validation was performed by 4 validators using a validation sheet. Student responses were collected using a questionnaire and reflective thinking skills using a multiple-choice test. The developed weblog has been tested on 20 students of 8th grade. The results showed that the use of blogging media positively impacted students' reflective thinking skills, given the increase in mean pre-test and post-test scores from a score of 69.5 to 82. The increase in reflective thinking skills was seen in of the three indicators of reflective thinking, namely reacting from 79% to 81,5% in the high category, elaborating from 50% in the low category to 75% in the high category, and contemplating from 67% in normal category to 78,4% in the high category. The use of blogging media to reinforce thinking skills is also supported by the results of student responses with an average result of 92,8% for aspects of reflective thinking